2005
DOI: 10.3354/meps303235
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of recreational fishing on behavior of the spiny lobster Panulirus argus

Abstract: Sublethal disturbance may lead to behavioral modifications that have detrimental consequences for the individual. Sublethal disturbance is an indirect effect of fishing that has seldom been examined. In summer 2003, we conducted surveys on the Caribbean spiny lobster Panulirus argus in the Florida Keys, USA, before and after a 2 d mini-season exclusively for recreational sportdivers to assess the frequency of injured lobsters. We also conducted (1) a tethering experiment to assess the influence of disturbance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…For example, Caribbean spiny lobsters avoid shelters containing damaged conspecifics, both in the laboratory and in the field (Parsons and Eggleston, 2005;Parsons and Eggleston, 2006;Bouwma, 2006;Briones-Fourzán et al, 2006;Briones-Fourzán and Lozano-Álvarez, 2008). Fishermen in Mexico avoid throwing spiny lobster bodies back in the water after removing their tails because this practice leads to a poor catch (Briones-Fourzán et al, 2006).…”
Section: Discussion Alarm Responses Of Spiny Lobsters To Hemolymphmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Caribbean spiny lobsters avoid shelters containing damaged conspecifics, both in the laboratory and in the field (Parsons and Eggleston, 2005;Parsons and Eggleston, 2006;Bouwma, 2006;Briones-Fourzán et al, 2006;Briones-Fourzán and Lozano-Álvarez, 2008). Fishermen in Mexico avoid throwing spiny lobster bodies back in the water after removing their tails because this practice leads to a poor catch (Briones-Fourzán et al, 2006).…”
Section: Discussion Alarm Responses Of Spiny Lobsters To Hemolymphmentioning
confidence: 99%
“…Decapod crustaceans also respond with alarm behavior to fluids leaked from injured conspecifics (Zimmer-Faust et al, 1985;Rittschof et al, 1992;Hazlett, 1994;Fleming et al, 2007). Caribbean spiny lobsters, Panulirus argus, have been reported to avoid fluids of injured conspecifics (Parsons and Eggleston, 2005;Parsons and Eggleston, 2006;Bouwma, 2006;Briones-Fourzán et al, 2006;Briones-Fourzán and Lozano-Álvarez, 2008). However, the source of chemical alarm cues from injured conspecifics and the immediate behavioral responses to such cues are poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Some shelters may contain conspecific chemical cues of aggregation but also alarm cues from injured conspecifics. Spiny lobsters are known to avoid shelters scented with fluids of injured or diseased conspecifics, or scents of predators (Berger and Butler, 2001;Parsons and Eggleston, 2005;Parsons and Eggleston, 2006;Behringer et al, 2006;Bouwma, 2006;Horner et al, 2008b).…”
Section: Conspecific Cues and Their Sensory Pathwaysmentioning
confidence: 99%
“…Fishing effort peaks during a 2 d mini-season for sport divers during the last week of July before the fishery opens to commercial and recreational fishers at the beginning of August. During this 2 d recreational fishery, 80-90% of legal sized lobsters present in targeted areas are removed (Eggleston et al 2003(Eggleston et al , 2008 and up to 27% of the remaining population of legal and sublegal lobsters may become visibly injured from interaction with sport divers (Parsons & Eggleston 2005). Lobster injury can result from either (1) an unsuccessful capture attempt, or (2) a successful capture and release of a sub-legal lobster.…”
mentioning
confidence: 99%
“…These injuries are detrimental to lobsters by reducing their growth (Davis 1981), causing direct mortality (Parsons & Eggleston 2005) and increasing exposure to predation by emigration from daytime shelters (Parsons & Eggleston 2006). Furthermore, the ability to attract other lobsters is eliminated when a lobster becomes injured (Parsons & Eggleston 2005).During underwater surveys of spiny lobsters in marine reserves and fished areas of the lower Florida Keys during summer 2004, we observed that the density of spiny lobster decreased by ~50% in fished areas from before to after the 2 d sport diver mini-season, yet increased ~3-fold in the relatively large and nearby Western Sambo marine reserve which contained high densities of relatively large lobsters (Fig. 1).…”
mentioning
confidence: 99%